R&D of the EM Calorimeter Energy Calibration with Machine Learning based on the low-level features of the Cluster - Morimasa Suzuna; Iwasaki Masako; Suehara Taikan; Tanaka Junichi; Saito Masahiko; Nagahara Hajime; Nakashima Yuta; Takemura Noriko; Nakano Takashi (EPJ Web of Conferences)
We have developed an energy calibration method using machine learning for the ILC electromagnetic (EM) calorimeter (ECAL), a sampling calorimeter consisting of Silicon-Tungsten layers. In this method, we use a deep neural network (DNN) for a regression to determine the energy of incident EM particles, improving the energy calibration resolution of the ECAL. The DNN architecture takes cluster hit data as low-level features of the cluster. In this paper, we report the status of our R&D and present results on energy calibration accuracy.